Maine's Bold Initiative: Homecare for All. Issue 3 (3rd April 2019) - Butler, Sandra
ABSTRACT: A 2018 ballot initiative in Maine proposed universal home care and improved work conditions for home care workers.Although ultimately defeated, the innovative proposal received considerable support and laid the groundwork for an upcoming legislative campaign.It offers a framework for increasing access to home care and creating quality jobs for home care aides. This commentary reviews the problems addressed by the Homecare for All initiative, what was proposed, the campaign process and anticipated next steps, and implications for gerontological social workers.